Род Smirnoviella (Crustacea, Cyclopidae) в Каспийском море с описанием нового вида - Монченко, В.И. (Вестник зоологии, 1982)
Smirnoviella unisetosa sp. nov. is described from the Northern Caspian Sea, between the Ural and Emba estuaries. It ditters rom S. reducta (an endemic sDecies of the Dniester estuary. black sea Dasin by a single middle apical seta on lurcal rami, reduction of the distal maxillar joint and a part o maxillular gnathobase appendages, etc. An emendation of generic diagnosis Is given.